Internships Help Marble Craft Craftsman Develop Creativity (Manjing) - Adin Ariyanti Dewi; Umi Dayati; Arif Wijayanto (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2022)
The purpose of this research is to determine the type of creativity of marble craftsmen in Gamping village through apprenticeship (Manjing) in the process of making marble crafts. This research employs qualitative methods and a phenomenological research approach. Data is gathered through observation techniques, interviews, and documentation. The data was analyzed in three stages: (1) data reduction, (2) data display, and (3) results withdrawal. Using extended attendance techniques, in-depth observation, and triangulation, the researcher determined the data's validity. The findings revealed that the process of creativity in making marble handicrafts was divided into three stages: 1) the input stage included growing interest and receiving information, 2) the process stage included processing information and attempting to make marble handicrafts, and 3) the output stage included self-evaluation conducted by apprentices.